How are health professionals earning their living in Malawi? - Maseko Fresier C; Muula Adamson S (BMC, 2006)
Abstract Background The migration of health professionals from southern Africa to developed nations is negatively affecting the delivery of health care services in the source countries. Oftentimes however, it is the reasons for the out-migration that have been described in the literature. The work and domestic situations of those health professionals continuing to serve in their posts have not been adequately studied. Methods The present study utilized a qualitative data collection and analysis method. This was achieved through focus group discussions and in-depth interviews with health professionals and administrators to determine the challenges they face and the coping systems they resort to and the perceptions towards those coping methods. Results Health professionals identified the following as some of the challenges there faced: inequitable and poor remuneration, overwhelming responsibilities with limited resources, lack of a stimulating work environment, inadequate supervision, poor access to continued professionals training, limited career progression, lack of transparent recruitment and discriminatory remuneration. When asked what kept them still working in Malawi when the pressures to emigrate were there, the following were some of the ways the health professionals mentioned as useful for earning extra income to support their families: working in rural areas where life was perceived to be cheaper, working closer to home village so as to run farms, stealing drugs from health facilities, having more than one job, running small to medium scale businesses. Health professionals would also minimize expenditure by missing meals and walking to work. Conclusion Many health professionals in Malawi experience overly challenging environments. In order to survive some are involved in ethically and legally questionable activities such as receiving "gifts" from patients and pilfering drugs. The efforts by the Malawi government and the international community to retain health workers in Malawi are recognized. There is however need to evaluate of these human resources-retaining measures are having the desired effects.